2017
DOI: 10.3389/fpls.2017.00098
|View full text |Cite
|
Sign up to set email alerts
|

VviAPRT3 and VviFSEX: Two Genes Involved in Sex Specification Able to Distinguish Different Flower Types in Vitis

Abstract: Vitis vinifera vinifera is a hermaphrodite subspecies, while its ancestor, Vitis vinifera sylvestris, is dioecious. We have identified two genes that together allow the discrimination between male, female and hermaphrodite Vitis plants. The sex locus region on chromosome 2 was screened resulting in the discovery of a new gene, VviFSEX. The same screening revealed another gene, VviAPRT3, located in the sex region, that be used as a sex marker. Both genes are good candidates to be involved in flower sex differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
35
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 24 publications
3
35
1
Order By: Relevance
“…7b). This is consistent with a previous study which showed that APT3 overexpression was specific to carpel primordia of sylvestris male flowers and led the authors to propose a role in carpel abortion (Coito et al, 2017). The ratio of expression between H/M and F alleles was predictably very low in female flowers which only contain the F allele, was low in hermaphrodite flowers, and was high in male flowers; the expression level or "dosage" of the APT3 H/M allele might influence sex determination (Extended Data Fig.…”
Section: Sex-linked Genes Have Distinct Expression Patterns and Are Hsupporting
confidence: 92%
See 2 more Smart Citations
“…7b). This is consistent with a previous study which showed that APT3 overexpression was specific to carpel primordia of sylvestris male flowers and led the authors to propose a role in carpel abortion (Coito et al, 2017). The ratio of expression between H/M and F alleles was predictably very low in female flowers which only contain the F allele, was low in hermaphrodite flowers, and was high in male flowers; the expression level or "dosage" of the APT3 H/M allele might influence sex determination (Extended Data Fig.…”
Section: Sex-linked Genes Have Distinct Expression Patterns and Are Hsupporting
confidence: 92%
“…In grapevine, cytokinin application restores normal female organ development, producing berries from male grapevine flowers (Negi and Olmo, 1966). Interestingly, APT3 expression has been previously associated with the abortion of pistil structures in male grapevine flowers because of the high expression of the gene in the third and fourth whorl of male flowers (Coito et al, 2017). Fig.…”
Section: Sex-linked Genes Have Distinct Expression Patterns and Are Hmentioning
confidence: 91%
See 1 more Smart Citation
“…Vitis is a perennial genus that in European countries has only one growing season, when it reiterates the development program allowing the analysis of the same plant on subsequent years. The present work in dioecious Vitis vinifera sylvestris (hereafter referred as V. v. sylvestris) lies in the difference between the two sexes: abortion of carpel development in male flowers and reflex stamens with non-viable pollen in female plants (Badouin et al, 2020;Coito et al, 2017;Massonnet et al, 2020;Picq et al, 2014;Zhou et al, 2017). We compared RNA edition events at several specific developmental stages, disclosing for the first time in plants, the twelve nucleotides modifications, previously detected in edited transcripts from human cells and cephalopods (Li et al, 2011;Liscovitch-Brauer et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Genetic analyses identified a 143-kb haplotype responsible for sex-determination in the grapevine reference genome 4, 5 . Two candidate genes for female sterility have been proposed, in particular APRT3 6 , a putative cytokinin regulator. However, the sequence of the sex locus was not available in V. sylvestris and no causative mutations have been identified.…”
Section: Figurementioning
confidence: 99%